Determining LBMP through Optimal Power Flow in the Electric Power Business - Hermagasantos Zein; Yusra Sabri; Erwin Dermawan (Institute of Advanced Engineering and Science, 2014)
The energy crisis has got the serious attention of experts since the middle19th century. Many efforts with significant progresses has been yielded to obtain its solution, such as technology development and diversification of primary energy sources, but the threat of the energy crisis has not been able to be avoided. Early tahun 1990, attention of experts are focused on energy savings, operating efficiencies and transparency. As a result, they have recommended changing the electric power business of the monopoly system to the market system, competition. In a competitive system, the problems will be more complex, especially in the energy price through optimization. One of the popular energy pricing methods today is LBMP, Locational Based Marginal Price, which has been successfully applied by New York, US. Generally, it is determined through ED, Economic Dispatch, calculations. In this case, Operator must do the complicated adjustments, especially for congestion conditions, so that thier results can be applied to the network. The simulation results, both heavy and light loads, showed that the OPF with step reduction can work well. Comparing with ED has to done some adjustments because a few contraints were out of their limits.